2021
DOI: 10.1007/s13340-021-00500-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features resembling subcutaneous insulin resistance observed in a patient with type 2 diabetes and severe COVID-19-associated pneumonia: a case report

Abstract: We report the case of a 52-year-old hyperglycemic woman with type 2 diabetes and severe coronavirus disease 2019 (COVID-19)-associated pneumonia, possibly involving the subcutaneous insulin resistance (SIR) syndrome. After admission for pneumonia, her average daily blood glucose (BG) levels remained at 300–400 mg/dL, although the required dosage of subcutaneous insulin markedly increased (~ 150 units/day; ~ 2.63 units/kg/day). Furthermore, the patient had generalized edema along with hypoalbuminemia, developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Considering these findings and the fact that our patients' maximal insulin requirements were lower than those of previous cases, despite the absence of apparent differences in BMI, this patient's insulin sensitivity may have been higher before the onset of COVID-19. The only case reported by Satomura et al was from East Asia, like our cases, but required high insulin doses, probably because of an unusual condition resembling insulin subcutaneous resistance syndrome [16]. Second, the administration of tocilizumab, an IL-6 receptor monoclonal antibody, might have affected insulin requirements.…”
Section: Discussionmentioning
confidence: 66%
“…Considering these findings and the fact that our patients' maximal insulin requirements were lower than those of previous cases, despite the absence of apparent differences in BMI, this patient's insulin sensitivity may have been higher before the onset of COVID-19. The only case reported by Satomura et al was from East Asia, like our cases, but required high insulin doses, probably because of an unusual condition resembling insulin subcutaneous resistance syndrome [16]. Second, the administration of tocilizumab, an IL-6 receptor monoclonal antibody, might have affected insulin requirements.…”
Section: Discussionmentioning
confidence: 66%
“…Paulsen et al 4 advised that clinical symptoms of SIR syndrome should be accompanied by no increase in the plasma-free insulin level and increased insulin degradation activity in subcutaneous tissues after subcutaneous injection. However, most reported cases of SIR syndrome were clinically diagnosed, and plasma-free insulin levels after administering a subcutaneous insulin injection 5 and insulin degradation at the tissue levels could not be determined in the cases 2 . Therefore, the diagnosis of SIR syndrome might not necessarily require changes in plasma-free insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous insulin and hypodermic insulin normally have similar effects 1 . It is rarely reported that a patient with hypodermic injection of insulin has no response, but intravenous injection has a good response, which is called subcutaneous insulin resistance (SIR) syndrome 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that increased HbA1c levels might be associated with dysregulated immune cell function 32,33 , fasting plasma glucose and HbA1c levels already increased on admission may reflect the aggravated inflammation of COVID-19 and the vulnerability to the inflammation, possibly leading to an increased risk of severity and mortality in patients with COVID-19. On the other hand, tight glycemic control using intravenous insulin infusion was shown to reduce disease severity and mortality in patients with COVID-19 and hyperglycemia 34,35 . These findings suggest that poor glycemic control on admission might lead to the severity of COVID-19-related pneumonia, and that early recognition and treatment of hyperglycemia may greatly benefit these patients.…”
Section: Demonstrated Thatmentioning
confidence: 99%